2020
DOI: 10.3390/ijerph17239098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In-Hospital Physical Therapy on Activities of Daily Living in Patients with Hepatocellular Carcinoma

Abstract: Activities of daily living (ADL) are frequently impaired in patients with hepatocellular carcinoma (HCC). In this retrospective study, we aimed to investigate the effects of physical therapy on ADLs in patients with HCC during hospitalization for cancer treatment. Nineteen patients with HCC were enrolled. During hospitalization, patients performed a combination of resistance training, stretching, and aerobic exercise (20–60 min/day). ADLs were assessed using the functional independence measure (FIM). Changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The results of a study in a population of elderly people showed that sarcopenia, defined by physical performance, muscle mass and muscle strength, is associated with impairment of higher-level functional capacity in daily living ( 49 ). In a cohort of adult cancer patients, a combined in-hospital physical therapy with resistance, aerobic, and stretching exercises improved muscle strength and functional independence regarding ADLs ( 50 ). Also a retrospective analysis among pediatric cancer patients identified that functional limitations in ADLs could be reduced through an inpatient rehabilitation program, including strength training during treatment ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study in a population of elderly people showed that sarcopenia, defined by physical performance, muscle mass and muscle strength, is associated with impairment of higher-level functional capacity in daily living ( 49 ). In a cohort of adult cancer patients, a combined in-hospital physical therapy with resistance, aerobic, and stretching exercises improved muscle strength and functional independence regarding ADLs ( 50 ). Also a retrospective analysis among pediatric cancer patients identified that functional limitations in ADLs could be reduced through an inpatient rehabilitation program, including strength training during treatment ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…The FIM score markedly increased after PA ( p = 0.0156), and especially the stairs index (5.9 vs. 6.4 points p = 0.024 before and after PA respectively). Thus PA improved muscle strength and ADL without worsening CLD [ 79 ]. In 2021, a multicenter study was conducted in Japan to assess the effect of in-hospital exercise on frailty in HCC patients.…”
Section: Role Of Physical Activity In Hccmentioning
confidence: 99%